Analysis of Income Tax Incentives (PPh) during the Covid-19 Pandemic in Indonesia - Albert Lodewyk Sentosa Siahaan (Universitas PGRI Madiun, 2021)
The Covid-19 pandemic since the beginning of 2020 has had a major impact on Indonesia's economic conditions. Due to the effects of the Covid-19 Pandemic, not a few companies have laid off or laid off their employees. In these circumstances, many people will no longer have income or have reduced income. Reduced income and the impact of the Covid-19 Pandemic on the economy greatly affected taxation, one of which was Income Tax (PPh). Income Tax (PPh) is a tax imposed on income received or earned by individual taxpayers or corporate taxpayers in one tax year. Therefore, the Indonesian government has implemented tax incentives for taxpayers affected by Covid-19. The government provides tax incentives with the aim of reducing the economic impact of the Covid-19 pandemic